P2Y2 Receptor Mediated Neuronal Regeneration and Angiogenesis to Affect Functional Recovery in Rats with Spinal Cord Injury. (2nd February 2022) - Cheng, Ruidong; Zhu, Genying; Ni, Chengtao; Wang, Rui; Sun, Peng; Tian, Liang; Zhang, Li; Zhang, Jie; Ye, Xiangming; Luo, Benyan
Abstract : The aim of this study was to investigate the effect of the P2Y2 receptor (P2Y2R) signaling pathway on neuronal regeneration and angiogenesis during spinal cord injury (SCI). The rats were randomly divided into 3 groups, including the sham+dimethyl sulfoxide (DMSO), SCI+DMSO, and SCI+P2Y2R groups. The SCI animal models were constructed. A locomotor rating scale was used for behavioral assessments. The apoptosis of spinal cord tissues was detected by TUNEL staining. The expression levels of P2Y2R, GFAP, nestin, Tuj1, and CD34 were detected by immunofluorescence staining, and the expression levels of TNF- α, IL-1 β, and IL-6 were detected by enzyme-linked immunosorbent assay. The locomotor score in the model group was significantly lower than the sham group. The expression of P2Y2R was increased after SCI. The expression levels of TNF- α, IL-1 β, and IL-6 were increased remarkably in the SCI model group compared with the sham group. The P2Y2R inhibitor relieved neuronal inflammation after SCI. Compared with the sham group, the apoptotic rate of spinal cord tissue cells in the model group was significantly increased. The P2Y2R inhibitor reduced the apoptosis of the spinal cord tissue. The expressions of CD34, Tuj1, and nestin in the model group were decreased, while the expressions of GFAP and P2Y2R were increased. The P2Y2R inhibitor reversed their expression levels. The P2Y2R inhibitor could alleviate SCI by relieving the neuronal inflammation, inhibiting the spinal cord tissue apoptosis, and promoting neuronal differentiation and vascular proliferation after SCI. P2Y2R may serve as a target for the treatment of SCI.